A Comparison of the 𝜶2/3/5 Selective Positive Allosteric Modulators L-838,417 and TPA023 in Preclinical Models of Inflammatory and Neuropathic Pain - Sarah Nickolls; Hannah Mace; Rebecca Fish; Michelle Edye; Rachel Gurrell; Magnus Ivarsson; Tom Pitcher; Sachi Tanimoto-Mori; Denise Richardson; Catherine Sweatman; Janet Nicholson; Cameron Ward; et al. (Hindawi Limited, 2011)
GABAA receptors containing α2/3 subunits are current targets in the battle to develop new pain medications, as they are expressed in the spinal cord where increasing inhibitory drive should result in analgesia. However, this approach is prone to a range of side effects including sedation, cognitive impairment, and abuse as a consequence of the widespread influence of GABA. The ability to make subtype selective low-efficacy benzodiazepine compounds, which potentiate the action of GABA at specific α subunits, has the potential to reduce this side effect profile. In this study, we have investigated the effects of the medium-efficacy positive allosteric modulator (PAM) L-838,417 and the low-efficacy PAM TPA023 in a number of preclinical inflammatory and neuropathic pain models. We conclude that either the higher level of efficacy at α2/3 or efficacy at α5 is required for compounds to have a significant analgesic effect in a range of models, and, therefore, although the side-effect profile of compounds can be reduced compared to typical benzodiazepines, it is unlikely that it can be completely eliminated.